The Evolution of Freedom of Testation in Post-Constitutional South Africa - Bapela, Mpho (Acta Universitatis Danubius. Juridica, 2024)
In South Africa, freedom of testation has been an enjoyed practice from ancient times. It gave testators comfort in knowing that when they depart, their legacies and property would be looked after by those they had chosen to survive their estates. Before the advent of the Constitution, testators used to abuse this freedom. There existed a tendency to exercise this freedom without limitations. However, the Constitutional epoch brought about changes in the manner the testators exercised their freedom of testation. Amongst other things, was the limitation to freedom of testation. Legislation and Common Law also contributed to restricting or limiting this freedom. Against this backdrop, this article investigates the impact of the Constitution on freedom of testation in South Africa under the current constitutional dispensation. The paper is predicated on the assumption that freedom of testation gave testators leeway to promote discrimination and unfairness. Therefore, this paper will show that freedom of testation has evolved and no longer absolute in South Africa, with the Courts playing an important role in the process.